A New Rictulariid (Nematoda: Spirurida) in Xenarthrans from Argentina and New Morphological Data of Pterygodermatites (Paucipectines) Chaetophracti - Ezquiaga, María Cecilia (2017)
Pterygodermatites is a cosmopolitan genus of nematodes from mammals, and it is frequently encountered in the parasite fauna of armadillos (Mammalia, Xenarthra, Cingulata). In this work, a new species, Pterygodermatites (Paucipectines) argentinensis, is described, and new morphometric data, new host records, and the geographical distribution of Pterygodermatites (Paucipectines) chaetophracti are provided. We examined 109 hosts belonging to Chaetophractus vellerosus, Chaetophractus villosus, Cabassous chacoensis, Dasypus hybridus, Tolypeutes matacus, and Zaedyus pichiy, from several regions of Argentina. Pterygodermatites (Paucipectines) argentinensis can be distinguished from P. (P.) chaetophracti by the morphology and size of esophageal teeth of both sexes, by subequal and longer spicules, by having only 1 precloacal cuticular semicircular fan in males, and by a greater number of cuticular processes in females. Cabassous chacoensis and Zaedyus pichiy are new hosts for Pterygodermatites (P.) chaetophracti.